Enhancing mathematical communication and Islamic values in Islamic and regular schools through interactive worksheets - Johar, Rahmah; Ikhsan, M.; Idami, Zahratul; Khairunnisak, Cut; Ellianti, Ellianti; Rohaizati, Ulya; Ghazali, Munirah (Frontiers in Education, 2025)
Mathematical communication skills are essential for helping students grasp mathematical concepts. Fostering students’ knowledge of Islamic values can also encourage them to relate mathematical topics to real-world situations, particularly in worship, enhancing their mathematical communication. Therefore, an innovative teaching approach is crucial to improving students’ mathematical communication and understanding of Islamic values. This study investigates the integration of these concepts within mathematics through the contextualized framework of Qurban. The study explores how an interactive worksheet can enhance mathematical communication skills and knowledge of Islamic values among junior high school students in Islamic and regular schools. Using a quantitative approach with a pretest-posttest control group design, the study involved 98 seventh-grade students from Banda Aceh, Indonesia, drawn from both school types. Two classes (experimental and control) from each school were randomly selected as samples. Data was collected using a mathematical communication test and a questionnaire on students’ knowledge of Islamic values. The data was analyzed using a t-test and MANOVA. This study revealed five key findings. First, a significant difference was found in the improvement of mathematical communication skills between students taught using interactive worksheets and those taught without them in the Islamic school. Second, a similar difference was observed in the regular school, where students taught using interactive worksheets demonstrated greater improvement in mathematical communication skills compared to those who were not. Third, no significant difference was identified in the improvement of knowledge of Islamic values between students taught with and without interactive worksheets in the Islamic school. Fourth, in contrast, a significant difference was found in the regular school, with students using interactive worksheets showing greater improvement in knowledge of Islamic values. Fifth, the type of school had no significant effect on the improvement of students’ mathematical communication skills or their knowledge of Islamic values. However, the use of interactive worksheets was found to have a significant effect on the improvement of both mathematical communication skills and knowledge of Islamic values. Thus, this study suggests that the effectiveness of interactive worksheets on students’ knowledge of Islamic values varies across different school contexts.